Masculinity and Help-Seeking Among Men With Depression: A Qualitative Study - Staiger, Tobias; Stiawa, Maja; Mueller-Stierlin, Annabel Sandra; Kilian, Reinhold; Beschoner, Petra; Gündel, Harald; Becker, Thomas; Frasch, Karel; Panzirsch, Maria; Schmauß, Max; Krumm, Silvia (Frontiers in Psychiatry, 2020)
Background: Many studies indicate that men are more reluctant to seek help for mental health problems than women. Traditional ideas of masculinity are often seen as a cause of this phenomenon. However, little is known about the diversity of experiences during the processes of help-seeking and service use among men with depression who have already utilized mental health services. This study aims to explore men’s experiences and attitudes towards depression, help-seeking and service use in order to develop gender-sensitive services. Methods: Narrative-biographical interviews were conducted with men treated for depression (n=12). Interview topics included individual experience with depression, help-seeking behavior and mental health service use. Transcripts were analyzed using qualitative content analysis. Results: Before seeking treatment, men’s help-seeking behavior was negatively affected by internalized masculine norms. However, findings indicate a change of attitudes towards depression after mental health service use. Men with depression emphasized a salutogenic perspective towards mental health problems and critically reflected on masculine norms. The positive function of men-only groups were described as key for successful service use. Conclusions: Men with depression reported experiences towards help-seeking and service use on four different levels: (i) attitudes towards depression, (ii) perception of societal views on depression, (iii) experiences within the family context and (iv) experiences with mental health services. Interventions to reduce the stigma of being “unmanly” and to improve men’s capacity to cope with being unable to work should be developed. Peer-led men-only groups may increase participants’ self-esteem and assist in disclosing weaknesses. In the context of GPs’ mediating role, training for health professionals concerning the impact of masculine norms on mental health is recommended.